Problem of cost analysis - Carrión Nin, José Luis (2000)
This article shows the most important problem of systems costs, which is the allocation of indirect costs to products. Note that there is an optimal system costs, but there is an alternative accounting system that gives administrators a detailed description of the costs of activities associated elements to the development of a product or a service otrogameinto; this system is more cost new technique called activity-based costing.